Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Problem Based Learning (PBL) Berbantuan Wordwall Kelas IV SDN 076/II Tenam Candi Kabupaten Bungo - Rizki, Dwi; Waldi, Atri; Anita, Yesi; Indrawati, Tin (Darul Yasin Al Sys, 2025)
The research aims to improve the learning outcomes of students in the Pancasila Education subject in the fourth grade of SDN 076/II Tenam Candi, Bungo Regency, through the implementation of the Problem Based Learning (PBL) model assisted by Wordwall. This study employs Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The results of the study show a significant improvement in student learning outcomes from the first cycle to the second cycle. The class average score increased from 67 in the first cycle to 86.15 in the second cycle, with the percentage of students achieving completeness rising from 54% to 92%. The PBL model has proven effective in enhancing student engagement and problem-solving skills through interactive learning that is relevant to daily life.